2002
DOI: 10.2527/2002.802367x
|View full text |Cite
|
Sign up to set email alerts
|

The provision of solid feeds to veal calves: II. Behavior, physiology, and abomasal damage1

Abstract: The aim of this study was to evaluate the effects of the addition of two roughage sources (wheat straw and beet pulp) to the milk replacer diet of veal calves, in order to reduce stress and improve animal welfare. We allocated 138 Polish Friesian male calves to three different feeding plans: a milk replacer diet (Control), 250 g/d of wheat straw in addition to the milk replacer, or 250 g/d of dried beet pulp in addition to the milk replacer. Within each feeding treatment, 16 calves were individually housed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
65
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 15 publications
(36 reference statements)
10
65
1
3
Order By: Relevance
“…The surface of abomasal damage increased with SF intake for an R:C ratio of 20:80 (P < 0.05), but not for 50:50 (interaction SF intake × R:C ratio: P = 0.11). Other studies showed that provision of SF to milk-fed calves increased the prevalence of abomasal damage, including pyloric ulcers, when compared with calves fed MR only (Breukink et al, 1991;Mattiello et al, 2002;Brscic et al, 2011). Solid feed particles may exert mechanically abrasive effects on the abomasal mucosa, which may be sensitized due to provision of large volumes of MR.…”
Section: Rumen Development and Abomasal Damagementioning
confidence: 94%
See 1 more Smart Citation
“…The surface of abomasal damage increased with SF intake for an R:C ratio of 20:80 (P < 0.05), but not for 50:50 (interaction SF intake × R:C ratio: P = 0.11). Other studies showed that provision of SF to milk-fed calves increased the prevalence of abomasal damage, including pyloric ulcers, when compared with calves fed MR only (Breukink et al, 1991;Mattiello et al, 2002;Brscic et al, 2011). Solid feed particles may exert mechanically abrasive effects on the abomasal mucosa, which may be sensitized due to provision of large volumes of MR.…”
Section: Rumen Development and Abomasal Damagementioning
confidence: 94%
“…Early rumen development is thought to increase utilization of SF in veal calves, especially toward the end of the fattening period (Berends et al, 2012b). However, the provision of SF to veal calves may increase the prevalence of abomasal lesions (Welchman and Baust, 1987;Mattiello et al, 2002;Brscic et al, 2011) and concentrate provision has been associated with ruminal drinking; that is, leakage of MR into the rumen (Berends et al, 2012b). Recently, it has been shown that urea recycling contributes to nitrogen retention in milk-fed calves provided with a low-protein SF (Berends et al, 2012a) but this contribution decreases with increasing protein content in the SF (H. Berends, unpublished data).…”
Section: Introductionmentioning
confidence: 98%
“…Veal calves develop abnormal oral behaviors such as excessive oral manipulation of the pen and abnormal rolling of the tongue, that is, tongue playing (Leruste et al, 2014), most likely due to an inadequate provision of solid feed (SF) and, in particular, insufficient structure in the SF (Mattiello et al, 2002;Webb et al, 2013;Leruste et al, 2014). It has been suggested that little structure limits natural rumination, which in turn leads to frustration and stress in the calves and ultimately to the development of abnormal oral behaviors (Mattiello et al, 2002;Webb et al, 2013;Webb, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Veal calves develop abnormal oral behaviors such as excessive oral manipulation of the pen and abnormal rolling of the tongue, that is, tongue playing (Leruste et al, 2014), most likely due to an inadequate provision of solid feed (SF) and, in particular, insufficient structure in the SF (Mattiello et al, 2002;Webb et al, 2013;Leruste et al, 2014). It has been suggested that little structure limits natural rumination, which in turn leads to frustration and stress in the calves and ultimately to the development of abnormal oral behaviors (Mattiello et al, 2002;Webb et al, 2013;Webb, 2014). Increased rumination can occur through increasing the provision of SF (Webb et al, 2012(Webb et al, , 2013, increasing the proportion of roughage or the presence of longer particles in the SF (Balch, 1971;Mertens, 1997;Kahyani et al, 2013), or providing coarser roughage sources (Mattiello et al, 2002;Webb et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation